Precarización vinculada al riesgo ambiental: revisión del caso La Loma en Cartagena de Indias (Colombia) - Joy Helena GONZÁLEZ-GÜETO (Revista Iberoamericana de Estudios de Desarrollo)
This article aims to deepen the debate around the precarization and marginalization experience of impoverished social groups in the Colombian Caribbean, associating these two categories of analysis to the risk of environmental disasters. Here we present a concrete experience of marginality linked to environmental risk, the case of La Loma in Cartagena, located on the highest hill of the city (La Popa) and designated by the authorities as «high risk area». The case was reviewed through the application of a preliminary survey, five semi-structured interviews to collect the stories of the villagers and a detailed examination of the official correspondence between Government institutions and community leaders. The results obtained allow us to affirm that the «environmental risk» is, for the authorities, a) the discursive framework that justifies interventions towards the eviction, but also b) the point of convergence of community identities linked to the territory. To situate the above, a specific experience of marginality linked to environmental risk, La Loma’s case, identified by the authorities of Cartagena as «high-risk landslide zone», located in the highest hill of the city, La Popa, will be reviewed.